الانسجام بين عناصر الحرف العربي الصوت، الرسم، المعنى حروف الإطباق أنموذج - سعداني, هناء (University of Eloued جامعة الوادي, 2015)
لقد حقق العربي درجة مبدعة من الانسجام بين نطقه لأصواته والتدليل عليها كتابة، مع أن هذه القدرة قد استخدمت في المراحل الأخيرة من تاريخ الحرف العربي، وذلك حين مكَّنه الذوق والحس المرهف – الذي منحته إياه بلاد العرب بعزلتها وطبيعتها الهادئة- من إعطاء أعلى صور الانسجام بين الرسم والصوت. فحين استلم العربي القلم وتعلم الكتابة، وجد نفسه قادرا على تحسين هذه الرموز التي تو ازي أصواته نطقا، فقلل من الانكسارات فيها، وأكثر الاستدارة، وقارب بين رموزه وأعضاء جهازه النطقي حين تؤدي هذه الأصوات، ثم وزع على هذه الحروف نقاطا بقدر ما يحمل هذا الصوت من مميزات فيزيائية، أو فيزيولوجية، فخصص لحرف نقطة واحدة أعلاه، وآخر اثن تين، وآخر ثلاثا، ونقط غيره واحدة أسفله وربما اثنتان، ليعبر عن حدث يضاهي نطقا موقع النقط وك مها، كل ذلك كان بتنسيق وانسجام بديعين.هذا ما يحاول هذا المقال إيضاحه من خلال حروف الإطباق: ص ض ط ظ The Arab has achieved a perfect degree of harmony between pronouncing his sounds and indicating on them in a written form, although this ability has been used in the late periods of the Arabic letter's history, and that is when the taste and the sens of slender - that the Arabic land has granted it to him by its isolation and its calm nature- have enabled him to give the highest images of harmony between the drawing and the sound. When the Arab has received the pen and has learnt writing, he found himself able to improve these symbols which equal his sounds in pronunciation, so he has reduced the angles in them, has increased the rotations and he has brought together his symbols and the components of of his vocal tracts when the latter is performing thes sounds, then he has distributed dots on these letters as much as this sound carries from physiological and physical features, so he has put a dot on the top of a letter, two and sometimes three on others, he has also dotted other letters with one dot in the bottom and maybe twoin order to express an event which equals in pronunciation the position of the dots and their quality. All this was with a splendid coordination and harmony. So it is not surprising to find that most of the Arabic letters show clearly the shape of the occurance of their sound from a certain side. That's what this article tries to explain through letters
Keywords: الانسجام، الحرف العربي، معنى الحرف; harmony, Arabic letter, meaning of letter